Comparative efficacy, toxicity and biodistribution of the liposomal amphotericin B formulations Fungisome® and AmBisome® in murine cutaneous leishmaniasis. Issue 2 (August 2018) - Wijnant, Gert-Jan; Van Bocxlaer, Katrien; Yardley, Vanessa; Harris, Andy; Alavijeh, Mo; Silva-Pedrosa, Rita; Antunes, Sandra; Mauricio, Isabel; Murdan, Sudaxshina; Croft, Simon L.
Abstract: Fungisome ® (F), a liposomal amphotericin B (AmB) product, is marketed in India as a safe and effective therapeutic for the parasitic infection visceral leishmaniasis. Its potential in the treatment of cutaneous leishmaniasis (CL), a disfiguring form of the disease affecting the skin, is currently unknown. Here, we report the evaluation of the efficacy of F in the Leishmania major BALB/c murine model of CL, including a head-to-head comparison with the standard liposomal AmB formulation AmBisome ® (A). Upon intravenous administration at dose levels of 5, 10 and 15 mg/kg of body weight (on days 0, 2, 4, 6 and 8), F showed clear signs of toxicity (at 15 mg/kg), while A did not. After complete treatment (day 10), the tolerated doses of 5 and 10 mg/kg F had significant antileishmanial activity (ED50 = 4.0 and 12.8 mg/kg for qPCR-based parasite load and lesion size, respectively), although less than that of A at identical doses (ED50 = 3.0 and 8.8 mg/kg). The efficacy of F was inferior compared to A because lower levels of the active agent AmB accumulated within the infected lesion. In conclusion, despite possibly being less safe and efficacious than A at equivalent doses, the moderate in vivo activity of F could indicate a role in the systemic pharmacotherapy of CL. Graphical abstract: Image 1